2019
DOI: 10.1212/wnl.0000000000007899
|View full text |Cite
|
Sign up to set email alerts
|

Motor cortex inhibition and modulation in children with ADHD

Abstract: ObjectiveCompared to typically developing (TD) peers, children with attention-deficit/hyperactivity disorder (ADHD) consistently demonstrate impaired transcranial magnetic stimulation (TMS)-evoked short interval cortical inhibition (SICI) of motor evoked potentials (MEPs) in resting motor cortex (M1). To determine whether perturbed M1 physiology also reflects clinically relevant behavioral dysfunction, we evaluated M1 physiology during a cognitive control task taxing motor response selection/inhibition.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 37 publications
5
50
0
Order By: Relevance
“…Within the larger sample that received TMS, we found that, compared with TD children, children with ADHD showed reduced SICI at rest and during the action-selection phase of the task (selecting to go or to stop), such that reduced SICI at rest does not resolve or normalize during engagement with this task. Additionally, we found that the amount of task-related up modulation (TRUM) of motor cortex excitability during this task was diminished in children with ADHD (Gilbert et al 2019). However, SICI and TRUM were only minimally correlated with one another (Zea Vera et al 2020), supporting the notion that these measures may be differentially sensitive to distinct mechanisms of altered physiology within ADHD.…”
mentioning
confidence: 86%
See 4 more Smart Citations
“…Within the larger sample that received TMS, we found that, compared with TD children, children with ADHD showed reduced SICI at rest and during the action-selection phase of the task (selecting to go or to stop), such that reduced SICI at rest does not resolve or normalize during engagement with this task. Additionally, we found that the amount of task-related up modulation (TRUM) of motor cortex excitability during this task was diminished in children with ADHD (Gilbert et al 2019). However, SICI and TRUM were only minimally correlated with one another (Zea Vera et al 2020), supporting the notion that these measures may be differentially sensitive to distinct mechanisms of altered physiology within ADHD.…”
mentioning
confidence: 86%
“…We therefore expected SICI-alpha ERD correlations in both groups and no interaction effect. Finally, within the larger TMS sample, children with ADHD showed less TRUM (Gilbert et al 2019). Within the larger ADHD sample, they showed less alpha ERD (McAuliffe et al 2020).…”
mentioning
confidence: 99%
See 3 more Smart Citations